THE STRUCTURE OF INDEPENDENT LEARNING IN HIGHER EDUCATION: STUDENTS’ ATTITUDE - Žydžiūnaitė, Vilma; Teresevičienė, Margarita; Gedvilienė, Genutė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The search for self-identity is a key determinant of postmodern society while correlating with the independent learning being conceptualized by the higher education students; it refers their intensions to express the ‘self’ and be identified. Most researchers have studied independent, self-directed, self-regulated and self-managed learning by paying attention to the different aspects covering learning styles, interactions, cognition, emotions, or volition, learning processes, metacognitive control system with the focus on students’ ability to direct, regulate and manage their independent learning. However, there is no research with the intention to explore the structure of the independent learning in higher education. Research results showed that despite perception of the independent learning structure the achievement of its outcomes cannot be ensured.